Ultrabroadband and High-Detectivity Photodetector Based on WS2/Ge Heterojunction through Defect Engineering and Interface Passivation - Wu, Di; Guo, Jiawen; Wang, Chaoqiang; Ren, Xiaoyan; Chen, Yongsheng; Lin, Pei; Zeng, Longhui; Shi, Zhifeng; Li, Xin Jian; Shan, Chong-Xin; Jie, Jiansheng (ACS nano, 2021)
Broadband photodetectors are of great importance for numerous optoelectronic applications. Two-dimensional (2D) tungsten disulfide (WS2), an important family member of transition-metal dichalcogenides (TMDs), has shown great potential for high-sensitivity photodetection due to its extraordinary properties. However, the inherent large bandgap of WS2 and the strong interface recombination impede the actualization of high-sensitivity broadband photodetectors. Here, we demonstrate the fabrication of an ultrabroadband WS2/Ge heterojunction photodetector through defect engineering and interface passivation. Thanks to the narrowed bandgap of WS2 induced by the vacancy defects, the effective surface modification with an ultrathin AlO x layer, and the well-designed vertical n–n heterojunction structure, the WS2/AlO x /Ge photodetector exhibits an excellent device performance in terms of a high responsivity of 634.5 mA/W, a large specific detectivity up to 4.3 × 1011 Jones, and an ultrafast response speed. Significantly, the device possesses an ultrawide spectral response spanning from deep ultraviolet (200 nm) to mid-wave infrared (MWIR) of 4.6 μm, along with a superior MWIR imaging capability at room temperature. The detection range has surpassed the WS2-based photodetectors in previous reports and is among the broadest for TMD-based photodetectors. Our work provides a strategy for the fabrication of high-performance ultrabroadband photodetectors based on 2D TMD materials.